Environmental ethics and uncertainty wrestling with wicked problems - Bauman, Whitney; O'Brien, Kevin J. (Kevin James) 1977- (Routledge, 2020)
"This book offers a multidisciplinary (theology, philosophy, and sociology) environmental approach to ethics in response to the contemporary challenge of climate change caused by globalized economics and consumption. This book synthesises the incredible complexity of the problem and the necessity of action in response, highlighting the unambiguous problem facing humanity in the 21st century, but arguing that it is essential to develop an ethics housed in ambiguity in response. Environmental Ethics and Uncertainty is divided into theoretical and applied chapters, with the theoretical sections engaging in dialogue with theorists and scholars from a variety of disciplines, while the applied chapters offer insight from 20th century activists who demonstrate and/or illuminate the theory, including Martin Luther King, Rachel Carson and Frank Lloyd Wright. This book is written for scholars and students in the interdisciplinary field of environmental studies and the environmental humanities, and will appeal to courses in religion, philosophy, ethics, politics and social theory"--